Mammalian esophageal stratified tissue homeostasis is maintained distinctively by the epithelial pluripotent p63+Sox2+ and p63−Sox2+ cell populations - Yu, Xiaohong; Yuan, Hui; Yang, Yanan; Zheng, Wei; Zheng, Xuejing; Lu, Shih-Hsin; Jiang, Wei; Yu, Xiying (Cellular and molecular life sciences : CMLS, 2023)
Self-renewing, damage–repair and differentiation of mammalian stratified squamous epithelia are subject to tissue homeostasis, but the regulation mechanisms remain elusive. Here, we investigate the esophageal squamous epithelial tissue homeostasis in vitro and in vivo. We establish a rat esophageal organoid (rEO) in vitro system and show that the landscapes of rEO formation, development and maturation trajectories can mimic those of rat esophageal epithelia in vivo. Single-cell RNA sequencing (scRNA-seq), snapshot immunostaining and functional analyses of stratified “matured” rEOs define that the epithelial pluripotent stem cell determinants, p63 and Sox2, play crucial but distinctive roles for regulating mammalian esophageal tissue homeostasis. We identify two cell populations, p63 + Sox2 + and p63 − Sox2 + , of which the p63 + Sox2 + population presented at the basal layer is the cells of origin required for esophageal epithelial stemness maintenance and proliferation, whereas the p63 − Sox2 + population presented at the suprabasal layers is the cells of origin having a dual role for esophageal epithelial differentiation (differentiation-prone fate) and rapid tissue damage–repair responses (proliferation-prone fate). Given the fact that p63 and Sox2 are developmental lineage oncogenes and commonly overexpressed in ESCC tissues, p63 − Sox2 + population could not be detected in organoids formed by esophageal squamous cell carcinoma (ESCC) cell lines. Taken together, these findings reveal that the tissue homeostasis is maintained distinctively by p63 and/or Sox2-dependent cell lineage populations required for the tissue renewing, damage–repair and protection of carcinogenesis in mammalian esophagi.